Health Status and Periodontal Care Needs of Pregnant Women in the Puger Coastal Area of Jember - Intan Nurun Azhria; Yuliana Mahdiyah Daat Arina; Melok Aris Wahyukundari; Kiswaluyo (Interdental Jurnal Kedokteran Gigi (IJKG), 2024)
Introduction: Pregnancy is a risk factor for periodontal disease due to an increase in hormones which causes a change in response of periodontal tissue to the accumulation of plaque and calculus that can increase the occurrence of inflammation of the gingiva and periodontal disease. Pregnant women in coastal areas have a high risk of periodontal disease because the majority consume seafood that contains high calcium and phosphorus, which allows for increased calculus formation. Periodontal disease during pregnancy has an adverse impact on the health of the fetus. Therefore, it is important to pay attention to the health of the periodontal tissues of pregnant women. This study aims to examine the description of health and periodontal treatment needs in pregnant women in the coastal area of Puger, Jember. Material and Methods: This type of research is descriptive observational with a cross sectional study on 70 subjects selected by purposive sampling technique. Data were obtained based on the results of the Community Periodontal Index of Treatment Needs (CPITN) examinations and questionnaire interviews regarding oral health. Results and Discussions: Health status of periodontal tissues of pregnant women in the coastal area of Puger Beach mostly (75,71%) had supra or subgingival calculus (CPITN score 2), there were periodontal pockets and there were no pregnant women with healthy periodontal tissue conditions. Types of periodontal treatment needs that are needed by all pregnant women are scaling and root planing and improving oral hygiene (Treatment Needs/TN 2).  Conclusion: Pregnant women in the coastal area of Puger Beach all experience periodontal disease so they need periodontal treatment.